Supply Chain Analysis A Handbook on the Interaction of Information, System and Optimization - Tang, Christopher S.; Tang, Christopher S.; Teo, Chung-Piaw.; Teo, Chung-Piaw.; Wei, Kwok-Kee.; Wei, Kwok-Kee. (International Series in Operations Research & Management Science,, 2008)
SUPPLY CHAIN ANALYSIS: A Handbook on the Interaction of Information, System, and Optimization is a carefully developed work focused on the analysis of supply chain interaction issues in emerging markets and industry sectors. It is a leading-edge handbook that will emphasize where little work has been done and where the "rubber meets the road" — the supply chain process, information, and systems integration. These are pertinent issues facing practitioners and researchers in today’s business environment. This is a gap-bridging handbook that analyzes interaction issues from both the research and practitioner sides. The result is a volume that examines and provides practical solutions on interaction issues while being firmly grounded in research principles. Some of the topical areas the Handbook examines are: The issue of supply chain design, from the perspective of foreign cosmetic companies in China; The issue of supply chain coordination among the grocery manufacturers. Most notably, the opportunity for strategic, multi-lateral collaboration through a shared distribution network; The impact of online secondary markets on the operational issues of a supply chain; The critical importance of risk and disruption in supply chain; and the huge issue of integrating demand and supply, hence the need to synchronize the supply chain with the demand chain.